If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3 = 0.7x + -2(0.4x + 1) Reorder the terms: -3 = 0.7x + -2(1 + 0.4x) -3 = 0.7x + (1 * -2 + 0.4x * -2) -3 = 0.7x + (-2 + -0.8x) Reorder the terms: -3 = -2 + 0.7x + -0.8x Combine like terms: 0.7x + -0.8x = -0.1x -3 = -2 + -0.1x Solving -3 = -2 + -0.1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.1x' to each side of the equation. -3 + 0.1x = -2 + -0.1x + 0.1x Combine like terms: -0.1x + 0.1x = 0.0 -3 + 0.1x = -2 + 0.0 -3 + 0.1x = -2 Add '3' to each side of the equation. -3 + 3 + 0.1x = -2 + 3 Combine like terms: -3 + 3 = 0 0 + 0.1x = -2 + 3 0.1x = -2 + 3 Combine like terms: -2 + 3 = 1 0.1x = 1 Divide each side by '0.1'. x = 10 Simplifying x = 10
| -6(-4)+10=-14 | | -2a-6=-28 | | (x*x)-7=(x*x)-6x-7 | | 1/u+1/v=1/f | | 4x^2+39x-42=0 | | (4y+8)-(4+3y)=7 | | 2/17x+14 | | 6/2/7 | | N/-10+7=10 | | 39x+89=39x+52 | | 4s+5-3/4s=3/4s-5 | | 2d=5d-18 | | 4n+3x=3 | | 19-(2x+3)=2(1x+3)+1x | | -(5x+6)-x=-6-6x | | -2k=63 | | 12x+5=104 | | 4x+x+1=8x-3x+1 | | 3/4x-1/4=13/4 | | 5y=-4-2y | | c-15=-4 | | 5-3x-7x+6x=0 | | -7=(1x-9)-3x | | 1.25x+30=2.50x+10 | | 1.7x-2.3(x+5.2)=-(11.8-x) | | 6x+2=5(x-3)+8 | | 3(3x+3)=12x+4-3x+5 | | 5=5(x-4) | | 12-4(2x-11)=-3(2x+4) | | m+3= | | 8=16+8x | | 17=37+4x |